2011
DOI: 10.1603/an10125
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Relationships and Relictualism of Rock-Crawlers (Grylloblattodea: Grylloblattidae) in Cave and Mountain Habitats of Korea

Abstract: Rock-crawlers (Grylloblattodea: Grylloblattidae) in northeastern Asia are low-vagility insects that are restricted to cool temperate forests and mountainous regions. Morphologically distinguishable species are similar ecologically and show narrow endemism and a patchy distribution. As a result, grylloblattids are hypothesized to be relict species that have persisted in situ over long periods of climatic and geological change (Storozhenko and Oliger 1984). We investigate whether the diversification pattern of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…It is likely that the divergence of these clades is related to this geographical history. Previous studies suggest that some extant Japanese insects and vertebrates may have originated in the late Miocene/Pliocene or during glacial periods (Kawamura, ; Sota & Hayashi, ; Yoshikawa et al ., ; Schoville & Kim, ; Schoville, Uchifune & Machida, ). Our study also suggests that E. shigae from the Asian continent may have colonized Japan at least during the late Late Miocene to Early Pliocene.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the divergence of these clades is related to this geographical history. Previous studies suggest that some extant Japanese insects and vertebrates may have originated in the late Miocene/Pliocene or during glacial periods (Kawamura, ; Sota & Hayashi, ; Yoshikawa et al ., ; Schoville & Kim, ; Schoville, Uchifune & Machida, ). Our study also suggests that E. shigae from the Asian continent may have colonized Japan at least during the late Late Miocene to Early Pliocene.…”
Section: Discussionmentioning
confidence: 99%
“…However, researchers have assumed that Grylloblatta dispersed to North America during the glacial cycles of the Pliocene–Pleistocene period, making use of the intermittent Beringian land bridge (Vrsansky et al , ; Jarvis & Whiting, ). While this hypothesis makes sense in light of their cold‐specialized ecology, recent genetic estimates of the divergence time between Grylloblatta and its Asian relatives are incompatible with the Pliocene–Pleistocene epochs (Schoville & Kim, ; Schoville et al , ). Instead, the estimated divergence time falls within the interval of 30–115 Ma (Schoville et al , ), suggesting that cold climatic episodes may have facilitated movement across the Bering land bridge during the Cenozoic period (Hopkins, ; Manchester, ).…”
Section: A Global Biogeography Of Grylloblattidaementioning
confidence: 99%
“…Specific accomplishments include clarification and extension of grylloblattid geographic distributions (Schoville, ; Schoville & Graening, ), species richness patterns (Kim & Lee, ; Bai et al , ; Schoville & Roderick, ; Schoville, ; Schoville et al , ), phylogenetic relationships (Klass et al , ; Terry & Whiting, ; Jarvis & Whiting, ; Schoville & Kim, ; Schoville et al , ) and morphological variation (Dallai et al , ; Uchifune & Machida, ; Wipfler et al , ) in Asia and North America. Problems revealed in Grylloblattidae systematics include uncertainty in the relationship of extant species to fossil ‘grylloblattids’ (Béthoux et al , ; Cui, ), paraphyly of the genera Namkungia Storozhenko & Park and Galloisiana Caudell (Schoville & Kim, ), the many undescribed cryptic species (Jarvis & Whiting, ; Schoville & Roderick, ; Schoville et al , ), and a highly divergent lineage of Galloisiana from northern Japan that may warrant generic status (Schoville et al , ). Resolving these taxonomic problems is necessary not only to facilitate further study of grylloblattid biology, but also, critically, for identifying and monitoring rare and potentially threatened species (Schoville & Graening, ).…”
mentioning
confidence: 99%
“…Surveys conducted throughout their range in northeast Asia and North America have identified new localities and filled distribution gaps (Schoville 2010). Genetic analyses have provided novel insights to the evolutionary biology of Grylloblattidae, providing the first phylogenetic analysis of generic relationships , new hypotheses for phylogenetic relationships to other insect orders (Terry & Whiting 2005), and an awareness of the utility of grylloblattid biogeography for understanding regional geological and climatic change (Schoville & Kim 2011, Schoville & Roderick 2010, Schoville et al 2013. The accumulation of this information suggests that grylloblattid species diversity has been underestimated and will likely increase in both Asia and North America.…”
Section: Introductionmentioning
confidence: 99%
“…However, phylogenetic analyses have shown that Galloisiana and Namkungia are not monophyletic clades (Schoville & Kim 2011, Schoville et al 2013, and Galloisiana yezoensis (Asahina 1961) from Hokkaido may be sufficiently divergent to warrant generic status. In contrast, North American grylloblattids (ice-crawlers) are strongly supported as comprising the monophyletic genus Grylloblatta Walker, 1914 based on genetic analyses Estimation of geographical distribution and natureserve and IUCN criteria.…”
Section: Introductionmentioning
confidence: 99%